How persistent is life satisfaction? Evidence from European immigration - Niclas Berggren; Andreas Bergh; Christian Bjørnskov; Shiori Tanaka (Research Institute of Industrial Economics (IFN), 2018)
This paper asks to what extent life satisfaction among immigrants remains similar to that in their country of origin and to what extent it adapts to that in their country of residence. We employ data from 29,000 immigrants in the European Social Survey to estimate the relative importance of these influences. We find evidence that the persistence of life satisfaction from the country of origin is strong for migrants from developed countries and close to zero for migrants from formerly communist countries. We also find that persistence for second-generation immigrants is similar but weaker than for their parents.
Keywords: I31; Z10; 330; Life satisfaction; Happiness; Life satisfaction; Heritability; Culture; Immigration